2017
DOI: 10.3892/mmr.2017.7011
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of JARID2 inhibits the viability and migration of placenta trophoblast cells in preeclampsia

Abstract: Protein Jumonji (JARID2) is a member of the Jumonji family of proteins and has been demonstrated to regulate cell proliferation and invasion. However, little is known about the role of JARID2 in the metastasis of placenta trophoblast cells. In the present study, the effect and the underlying molecular mechanism of JARID2 on trophoblast cell viability and invasion was investigated. The expression of JARID2 in placental tissues was analyzed by reverse transcription‑quantitative polymerase chain reaction and west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Additionally, the potential therapeutic significance of JARID2 in addressing Preeclampsia has been proposed. This proposition is grounded in the observed inhibitory effects of JARID2 on the viability and migration of placental trophoblast cells, as elucidated in previous research (64).…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, the potential therapeutic significance of JARID2 in addressing Preeclampsia has been proposed. This proposition is grounded in the observed inhibitory effects of JARID2 on the viability and migration of placental trophoblast cells, as elucidated in previous research (64).…”
Section: Discussionmentioning
confidence: 64%
“…Efficient trophoblastic infiltration forms the basis for the effective establishment of uteroplacental circulation and is key to successful pregnancy ( 33 ). Insufficient invasion and migration of trophoblast cells results in shallow embryo implantation, inadequate placental invasion and abnormal spiral artery remodeling, which are generally regarded to be major mechanisms underlying PE ( 34 ). To the best of our knowledge, the present study is the first to explore the effects of PAD4 on the invasion and migration of HTR8/SVneo cells following exposure to LPS, where PAD4 silencing promoted the invasion and migration of HTR8/SVneo cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism via which draM1 induces apoptosis or autophagic apoptosis remains unclear. in addition, it has been reported that inflammation-associated apoptosis is regulated by Bcl-2 and Bax (63,64), and that decreased invasion and migration ability of trophoblast cells induced by cell apoptosis in the placenta may be the major causes of PE (65,66). Therefore, the specific mechanism of DRAM1 and the relationship of between inflammation and Bcl-2 and Bax requires further investigation.…”
Section: Discussionmentioning
confidence: 99%